Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan Pada PT Millennium Pharmacon International, Tbk - Vina Octafia Andini; Ety Nurhayaty (PT. Karya Inovatif Nusantara, 2025)
Employee performance is one of the most important factors for the progress of the company. Companies are required to be able to manage and organize their resources effectively and efficiently. Whether or not a company develops can be determined by the performance of the company's employees. Good employee performance can make the company more advanced. One of them is the provision of rewards and punishments is one of the factors that help improve employee performance to be better. The purpose of this study was to determine and analyze the effect of Reward and Punishment variables on Employee Performance. The method used is Quantitative Statistics using saturated sampling of 48 people. The questionnaire is the main instrument for collecting primary data. The research analysis uses multiple linear regression assisted by SPSS version 25.0. The results of the research analysis show that rewards partially have a positive and significant effect on employee performance, punishments partially have a positive and significant effect on employee performance, and rewards and punishments simultaneously have a positive and significant effect on employee performance at PT Millennium Pharmacon International, Tbk